Amazon floodplain hydrology and implications for aquatic conservation. Issue 5 (11th March 2021) - Melack, John M.; Coe, Michael T.
Abstract: The amplitude, duration, frequency, and predictability of runoff and inundation of aquatic habitats are key hydrological characteristics linked to aquatic ecosystem functioning and biodiversity, but they are seldom integrated into analyses of Amazon floodplain ecology. Remote sensing approaches, measurements and modelling of floodplain hydrology provide a basis for this integration. Effective legislation to protect floodplains and other wetlands depends on operational definitions that require application of hydrological data. Extent and changes of flooded areas are linked to fish diversity and to presence and growth of flooded forests and floating plants. Dam construction reduces river system connectivity and modifies the flood pulse, with major negative implications for floodplain ecosystems adapted to and dependent on a natural flood regime. Trends and variability in climate plus deforestation are altering the Amazon's hydrological cycle, causing changes in discharge and flooded area with concomitant ecological impacts.